Analisis Penerapan Psap Nomor 07 Tentang Aset Tetap Pada LKPD Kabupaten Sleman Tahun 2021 – 2023 - Nita Nur Halimah; Nopi Tikasari (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The objective of this study is to analyze the implementation of Government Accounting Standards Statement (PSAP) Number 07 on Fixed Assets in the Government of Sleman Regency during the period 2021–2023. The study employs a descriptive qualitative approach using secondary data obtained from the Audit Reports (LHP) issued by the Audit Board of Indonesia (BPK) on the financial statements of Sleman Regency. The analysis is conducted through document content analysis to examine findings, audit notes, and recommendations presented in the reports to assess the level of compliance with PSAP 07. The results indicate that the Government of Sleman Regency has consistently applied PSAP 07 in the recognition and measurement of fixed assets, although shortcomings still exist in the presentation and disclosure aspects, particularly related to incomplete Asset Inventory Cards (KIB) and delays in land certification. The audit reports also note improvements in administrative capacity compared to previous years, even though the quality of asset disclosure still requires enhancement. The increase in land asset value from IDR 1.57 trillion in 2021 to IDR 1.80 trillion in 2023 reflects improvements in asset inventory processes and valuation. The findings of this study are expected to provide empirical contributions to improving fixed asset governance and serve as an evaluation resource for local governments in their efforts to enhance the quality of financial reporting.